Penerapan Desain UI/UX pada Aplikasi Web Portal Berita Dengan Metode Design Thinking - Melanda Sari; Reflan Nuari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid advancement of technology and digitalization has significantly transformed how people access information, making web applications a primary platform for reading news. In this context, User Interface (UI) and User Experience (UX) design play crucial roles in determining the success of a news platform. This study aims to explore the application of the Design Thinking method in designing the UI/UX of the Paparan Lampung news application to enhance reader engagement and optimize user experience. The Design Thinking approach was chosen because it focuses on user needs through stages of empathy, problem definition, ideation, prototyping, and testing, enabling the creation of relevant and innovative design solutions. This research employs a descriptive quantitative method, utilizing the System Usability Scale (SUS) to assess the application’s usability level. The results show that Paparan Lampung achieved a SUS score of 88.5, categorized as “Excellent” (Grade A) and exceeding the industry acceptance threshold of 68. Furthermore, the MAUS score of 80.3 reinforces that the application is not only efficient and effective but also delivers a highly satisfying user experience. Overall, the implementation of Design Thinking has proven to enhance UI/UX design quality, directly improving user comfort and engagement. Despite the highly positive results, this study has limitations in terms of the number of respondents and the controlled testing environment. Therefore, future research is recommended to involve a larger and more diverse group of participants to obtain more comprehensive and generalizable findings.